(untitled) (Global Journal of Science Frontier Research, 2018)
In this paper, the quantum properties of an electrically pumped non-degenerate three level laser with two mode subharmonic generator coupled to a two-mode vacuum reservoirs via a single-port mirror whose open cavity contains N non-degenerate three-level cascade atoms is presented. The analysis is carried out by putting the noise operators associated with a vacuum reservoir in normal order. It is found that the photons as well as atoms of the system are strongly entangled at steady state. It has been shown that the degree of photon entanglement greater than that of atom entanglement. Moreover, the presence of the subharmonic generator leads to an increase in the degree of entanglement.